2021
DOI: 10.35848/1347-4065/abeff2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of leaky surface acoustic wave harmonics excitation using bonded dissimilar-material structures

Abstract: The enhancement of high-order surface acoustic wave (SAW) harmonics by increasing the metallization ratio was theoretically and experimentally investigated in high-performance bonded dissimilar-material structures. The simulation using a finite element method for 36°Y-cut X-propagating LiTaO3 (36°YX-LT)/AT-cut 90°X-propagating quartz (AT90°X-quartz) and 27°YX-LiNbO3/AT90°X-quartz was performed by setting the metallization ratio of the interdigital transducer to a/p = 0.8 (a: electrode width, p: pitch), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Moreover, the excitation of third harmonics can be enhanced and resonance properties similar to those of the fundamental wave on a single LT or LN substrate can be obtained at a frequency three times higher than that of the fundamental wave by utilizing bonded structures comprising a quartz substrate and an LT or LN thin plate. 92) The structures can also be applied to acoustooptic 93) and sensor devices. In the future, substrate structures that further increase the performance of SAW devices will be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the excitation of third harmonics can be enhanced and resonance properties similar to those of the fundamental wave on a single LT or LN substrate can be obtained at a frequency three times higher than that of the fundamental wave by utilizing bonded structures comprising a quartz substrate and an LT or LN thin plate. 92) The structures can also be applied to acoustooptic 93) and sensor devices. In the future, substrate structures that further increase the performance of SAW devices will be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A perfect matching layer (PML) was provided at the bottom of the substrate. 35,36) The mechanical loss Q m and dielectric loss were not taken into consideration. The ScAlN film thickness was set to the film thickness at which K 2 was maximized in the theoretical analysis shown in Table I.…”
Section: Fem Analysismentioning
confidence: 99%
“…Recently, to satisfy such requirements, high-performance dissimilar-material bonded structures have been proposed. 4,8,[14][15][16][17][18][19][20][21][22] For example, spurious-free, steep attenuation, and good TCF have been reported in heteroacoustic layer (HAL) SAW resonators with 25°YX-LT bonded to a 42°45′Y90°X-Qz support substrate. 14) Furthermore, it is theoretically shown that in the ScAlN/Qz structure, high Q and high coupling can be obtained on an LSAW by using appropriate film thicknesses and Euler angles.…”
Section: Introductionmentioning
confidence: 99%